Neurological Manifestations in Leprosy: A Study in Tribal Community of Hill Tracts (Journal of Enam Medical College, 2016)
Background: Leprosy is a chronic granulomatous infectious disease having major burden on humans over thousands of years. If untreated, it results in permanent damage to various systems and organs. So we designed this study to evaluate the neurological complications in early stage in adult leprosy patients.Objective: The aim of this study was to find out the pattern of neurological manifestations among adult leprosy patients.Materials  and  Methods: This cross-sectional hospital-based study on 85 adult tribal leprosy patients was conducted in a district level health care facility from January to December 2014 using simple, direct, standardized questionnaire including history and neurological examinations.Results: The commonest age group affected was 1830 years (62.4%). Male group was predominant (68.2%). Majority cases (66%) had multibacillary leprosy. At first visit 72.7% cases with neurological findings could not be diagnosed correctly by primary health care personnel. More than six months were required for correct diagnosis in 61.2% cases. Numbness was the commonest (74.5%) neurological symptom. In upper limb, motor findings were predominant with wasting in 50.9% cases. In lower limb, sensory findings were predominant with stock pattern sensory impairment being the commonest (56.4%). Ulnar nerve was the commonest peripheral nerve to enlarge with tenderness. Facial nerve was the commonest cranial nerve involved. All cases with multiple cranial nerves involvement were of multibacillary type. Due to physical disability 92.7% cases lost their jobs.Conclusion: In this study neurological involvement was found associated with severe disability.J Enam Med Col 2016; 6(1): 10-14